Children with transfusion dependent thalassaemia : the study of psychological distress and coping strategies among caretakers - Ghani, Mohd. Sufian Ardi Abd. (2016)
Introduction: Hemoglobin E beta thalassaemia is prevalent in Malaysia. Knowing thalassaemia is a chronic disease it is a lifelong burdens not only to the patient but also to the parent and other caretakers. Psychological distress is manifested in multiple ways and at different level of severity. Therefore coping strategies are developed in order to reduce the stress hence ascertain a high quality of life. Objectives: The aim of this study were to determine the mean psychological distress level and brief COPE of caretakers, to compare mean psychological distress level with brief COPE and income status and to identify the associated factors for psychological distress and brief COPE respectively. Methodology: DASS 21 and brief COPE questionnaires. 3.54). Stress mean score was (4.25, SD 3.26). The highest mean score for brief COPE was religion (7.00, IQR 2.00). Depressive caretakers had significant score for substance use (4.50, IQR 3.00). Meanwhile anxious caretakers had significant score for denial (5.50, IQR 3.00), substance use (4.00, IQR 4.00) and behavior disengagement (4.00, IQR 3.00). There was no significant difference between psychological distress and income status. Age, gender, education, working and income status were identified to have association with brief COPE. Conclusion: Majority of caretakers had utilized religion coping, meanwhile substance use, denial and behavioral disengagement were utilized by depressive and anxious caretakers. Scoring for DASS 21 showed no significant different between two groups of income. Brief COPE was associated with age, gender, education, working and income status.